2021
DOI: 10.1371/journal.pone.0252940
|View full text |Cite
|
Sign up to set email alerts
|

What predicts the early sexual debut among unmarried adolescents (10–19 years)? Evidence from UDAYA survey, 2015–16

Abstract: Introduction The societal norm in India is such that adolescents are expected to respect and follow traditional values and view early sexual debut as undesirable and deviant from the social mores. However, a dramatic shift in attitudes towards sex before marriage has been observed in India. We in this study, aim to study the factors associated with early sexual debut among unmarried adolescents. Materials and methods The study used data from the Understanding the lives of adolescents and young adults (UDAYA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
2
14
1
1
Order By: Relevance
“…The government of Uganda should also make the media affordable and accessible to all youth, to positively empower them with sex and reproductive health information in the early stages of their development before their sexual debut for improved sexual health. Contrary to our findings, research conducted in other settings shows that male youth who had frequent media exposure were significantly more likely to engage in early sexual debut than those who had no media exposure [49].…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…The government of Uganda should also make the media affordable and accessible to all youth, to positively empower them with sex and reproductive health information in the early stages of their development before their sexual debut for improved sexual health. Contrary to our findings, research conducted in other settings shows that male youth who had frequent media exposure were significantly more likely to engage in early sexual debut than those who had no media exposure [49].…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…Following Ghana’s Criminal Code (amendment) Act, 2003 (Act 646) [ 4 ], the outcome variable for the analysis was binary coded 1 if a woman aged between 15 and 49 years had her first sexual intercourse before attaining 16 years of age and 0 otherwise. The covariates for the analysis were selected based on evidence from the literature [ 2 , 7 , 12 , 29 , 30 ] and their availability in the GMHS data. The covariates were grouped into three categories: demographic, socioeconomic and pregnancy outcome factors to examine their associations with the spatial patterns of early sexual debut at the district level.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in two states in India found that 9% of the boys and 4% of the girls in adolescent age, engaged in early sexual debut. The same study also found that the prevalence of early sexual debut was more among boys than girls and among school drop outs compared to schooling adolescents (10).…”
Section: Discussionmentioning
confidence: 73%